Impact of Tobacco Control Policy on Quitting and Nicotine Dependence among Women in Five European Countries - Allen, JA (2012)
OBJECTIVE: Describe differences in and factors associated with former smoking and nicotine dependence among women in Ireland, Sweden, France, Italy and the Czech Republic. METHODS: A cross-sectional, random digit dial telephone survey of 5000 women, ages 18 and older, conducted in 2008. Analyses were conducted using logistic regression models. RESULTS: Respondents from Ireland and Sweden had statistically significantly higher odds of having quit smoking within the 5 years prior to survey administration as compared with respondents from the Czech Republic. Current smokers from Ireland, Sweden, France and Italy are more nicotine dependent than those from the Czech Republic. CONCLUSIONS: Respondents from countries with stronger tobacco control policies were more likely to be have quit smoking compared with those living in the Czech Republic. However, respondents in countries with some of the strongest policies (Ireland, Sweden, France and Italy) had higher odds of smoking within 30 minutes of waking, an established indicator of nicotine dependence. More research in this area is warranted, but this study suggests that: 1) now that the Czech Republic is beginning to implement strong tobacco control policy, they will likely achieve a rapid decline in population-level smoking; and 2) Ireland, Sweden, France, Italy and other countries with established, strong tobacco control policies would do well to consider what additional programs they can put in place to help their highly nicotine dependent population of smokers successfully quit.